The TANF Resources Problem. Issue 1 (March 2017) - Meni, David; Wiseman, Michael
Abstract : The year 2016 marked the twentieth anniversary of the Personal Responsibility and Work Opportunity Reconciliation Act (PRWORA), which replaced the Aid to Families with Dependent Children program (AFDC) with Temporary Assistance for Needy Families (TANF). Whereas AFDC was based on an open‐ended matching grant, TANF is funded with a block grant from the federal government and "maintenance of effort" (MOE) obligations for states, which were generally set at 75 percent of nominal expenditures in the mid‐1990s. This article looks at trends in TANF funding compared to trends in child poverty. We include a more comprehensive poverty measure and adjustments for interstate variation in prices. Over the past decade, inequality in state resources per poor child has increased. The disparities are great, making application of uniform TANF work participation standards to all states without adjustment for variation in resources questionable. The article concludes with an exploration of the connection between TANF resources and state fiscal capacity and a discussion of options for reform.